Modelling of marine traffic flow complexity. (1st August 2015) - Wen, Yuanqiao; Huang, Yamin; Zhou, Chunhui; Yang, Junlan; Xiao, Changshi; Wu, Xiaochun
Abstract: Recent increases in the number of high-speed, large-scale, and heavy-load vessels have made marine traffic more complex. Traffic situations are more difficult to manage as a result because of the rapid increase in the traffic density and the development of ship encounter situations. Here, we introduce a marine traffic complexity model to evaluate the status of traffic situation, use the complexity to investigate the degree of crowding and risk of collision, and support mariners and traffic controllers to get the traffic situation awareness. The traffic unit complexity model is constructed using pair-wise ship traffic characteristics such as the relative distance, relative speed, and intersecting trajectory. This model is extended to an area traffic complexity model through interpolation post-processing. We show that a higher complexity corresponds to more crowding and dangerous traffic in which the traffic situation should be carefully managed. Simulated data from the Shenzhen West Sea are employed to demonstrate the model and construct a map of the spatial distribution of the marine traffic complexity. The complexity model is shown to be effective in indicating different traffic situations. Highlights: The marine traffic complexity model is introduced to investigate the degree of crowding and risk of collision. The complexity model is constructed by analysing traffic characteristics. The simulated traffic data are employed to validate the model. The complexity map of simulated traffic scenario illustrates the spatial distribution of the marine traffic complexity.